2021
DOI: 10.3390/rs13030413
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Multi-Angle Remote Sensing and Its Application in Urban Land Cover Classification

Abstract: Because of the limitations of hardware devices, such as the sensors, processing capacity, and high accuracy altitude control equipment, traditional optical remote sensing (RS) imageries capture information regarding the same scene from mostly one single angle or a very small number of angles. Nowadays, with video satellites coming into service, obtaining imageries of the same scene from a more-or-less continuous array of angles has become a reality. In this paper, we analyze the differences between the traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Second, data sources were dimensionally limited; we only obtained 2D multispectral data. Further studies of multi-angle multispectral data may be helpful (Wang R. et al, 2021;Yuan et al, 2021), indicating that more information on the distribution of spectral values in the middle and lower parts of canopy would be learned by the model. Moreover, the spectral class was limited, fusion and inversion with hyperspectral images will provide richer spectral information (Xu, 2023), thereby extending the 3D spectral breadth of forests in terms of species.…”
Section: Future Improvementsmentioning
confidence: 99%
“…Second, data sources were dimensionally limited; we only obtained 2D multispectral data. Further studies of multi-angle multispectral data may be helpful (Wang R. et al, 2021;Yuan et al, 2021), indicating that more information on the distribution of spectral values in the middle and lower parts of canopy would be learned by the model. Moreover, the spectral class was limited, fusion and inversion with hyperspectral images will provide richer spectral information (Xu, 2023), thereby extending the 3D spectral breadth of forests in terms of species.…”
Section: Future Improvementsmentioning
confidence: 99%
“…It is simply defined as labeling an aerial image with a semantic category according to the image content. With the fast development of deep learning, most existing studies [19][20][21][22][23] have shown great success. These methods are all the singlelabel image classification.…”
Section: A Aerial Image Processing Tasksmentioning
confidence: 99%
“…Remote sensed data has become the pillar for all kinds of land observation tasks [2,3]. Given the availability of such data and thanks to deep learning methods, different kinds of implementations have emerged in domains such as agriculture, urban development and environmental purposes [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%